Using 3D virtual worlds to support geographically distributed software development team - Chang, Vanessa; Guetl, Christian; Hadzic, M. (Universidad Carlos III de Madrid, 2011)
Today’s software development projects are generally performed by development teams that are geographically distributed. This trend also introduces a number of complications when it comes to communication between stakeholders, coordination of work, and control of the project. This paper reports on a prototype of an environment in a 3D virtual world which supports distributed software teams working on tasks. In this environment, virtual team members share a common space, communicate through multiple communication channels and have better team awareness, which ultimately helps them to complete software projects. This paper elaborates on the complexities within distributed teams as well as the different technologies that were employed to connect geographically dispersed co-workers. The requirements of the software development processes are implemented in the virtual world prototype to enable distributed teams to perform their work efficiently. The prototype is based on Sun’s Project Wonderland. A study involving developers and users was conducted which shows that the environment in virtual worlds can support the software development and project management disciplines in distributed settings. Richer and numerous communication possibilities, different applications and the ability to work with colleagues in a shared space help distributed software teams to overcome the barriers of physical separation.